The Impact of Intellectual Capital, Digital Literacy and Digital Transformation on MSME Performance: The Mediating Role of Edupreneurship Innovation in Malang City - Intan Umull Magfira Sary; Wening Patmi Rahayu; Madziatul Churiyah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
Micro and Small Enterprises (MSEs) play a strategic role in the Indonesian economy; however, they continue to face challenges in improving performance and competitiveness in the digital economy era. These challenges are closely related to limitations in intellectual capital management, low levels of digital literacy, and the suboptimal implementation of digital transformation, which weaken business innovation, particularly among Food and Beverage (F&B) sector MSEs in Malang City. From the perspective of educational and educational management, these conditions indicate the need for systematic entrepreneurship education, digital literacy learning, and well-managed training programs to strengthen the competencies and adaptive capacities of MSE actors. This study aims to analyze the influence of intellectual capital, digital literacy, and digital transformation on MSE performance, with Innovation edupreneurship as a mediating variable, based on Dynamic Capability Theory and supported by educational management approaches emphasizing learning processes, knowledge development, and entrepreneurial capacity building. This quantitative research employed an explanatory design with a cross-sectional survey of 373 MSE owners selected from a population of 11,929 F&B MSEs in Malang City. Data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with SmartPLS 4.0. The findings show that intellectual capital significantly improves MSE performance, while digital literacy and digital transformation do not directly affect performance. However, all three variables significantly influence innovation. Innovation edupreneurship also positively affects performance and mediates the relationships between intellectual capital, digital literacy, digital transformation, and MSE performance. These findings highlight the strategic role of educational management through entrepreneurship education, digital literacy programs, and continuous training in strengthening Innovation edupreneurship capacity and improving the sustainable performance of MSEs.